Cytochrome P450 enzymes in the black-spotted frog (Pelophylax nigromaculatus): molecular characterization and upregulation of expression by sulfamethoxazole - Liu, Zhiqun; Shi, Chaoli; Wang, Bingyi; Zhang, Xiaofang; Ding, Jiafeng; Gao, Panpan; Yuan, Xia; Liu, Zhiquan; Zhang, Hangjun (Frontiers in Physiology, 2024)
Cytochrome P450 (CYP) enzymes are crucial for the detoxification of xenobiotics, cellular metabolism, and homeostasis. This study investigated the molecular characterization of CYP enzymes in the black-spotted frog, Pelophylax nigromaculatus, and examined the regulation of CYP expression in response to chronic exposure to the antibiotic sulfamethoxazole (SMX) at various environmental concentrations (0, 1, 10, and 100 μg/L). The full-length cDNA of Pn-CYP26B1 was identified. The sequence included open reading frames of 1536 bp, encoding proteins comprising 511 amino acids. The signature motif, FxxGxxxCxG, was highly conserved when compared with a number of selected animal species. SMX significantly upregulated the expression of the protein CYP26B1 in frog livers at concentrations of 1 and 10 μg/L. SMX showed an affinity for CYP26B1 of -7.6 kcal/mol, indicating a potential mechanism for SMX detoxification or adaptation of the frog. These findings contributed to our understanding of the environmental impact of antibiotics on amphibian species and underscored the importance of CYP enzymes in maintaining biochemical homeostasis under exposure to xenobiotic stress.